Оcобливості призначення покарання неповнолітнім за наявності обставин, що пом’якшують покарання - Чупринський, Б.; Chupryns’kyi, В. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджуються особливості призначення покарання неповнолітнім за наявності обставин, які пом'якшують покарання, передбачених Загальною частиною Кримінального кодексу України. Розглядається гуманізація кримінального законодавства щодо призначення покарання неповнолітнім, забезпечення охорони основних прав і свобод неповнолітнього злочинця. Аналізується вік кримінальної відповідальності, обов'язковості врахування пом'якшуючих обставин і індивідуальний підхід при призначенні покарання. Призначення покарання з урахуванням ступеня тяжкості вчиненого злочину, особи неповнолітнього та обставин, що пом’якшують чи обтяжують покарання, повинно максимально сприяти досягненню мети покарання, яка полягає у виправленні неповнолітнього засудженого, його вихованні й соціальній реабілітації. The emphasis is laid on the humanization of criminal legislation on sentencing juveniles, ensuring the protection of the fundamental rights and freedoms of a juvenile offender, specification of the age of criminal responsibility, obligatoriness of taking into account mitigating circumstances and individual approach to sentencing. The individualization of punishment is an important requirement of the principle, which anticipates personification of thecriminal responsibility: it can be applied only toa concrete person who committed the crime in every separate case. Sentencing according to the severity of the offense and the personal peculiarities of a minor, as well as taking into account the circumstances mitigating or aggravating the offence, will allow to realize the penalty goal in the best possible way, which implies correcting the juvenile convict, his behavior and his social rehabilitation. The Court must carefully and thoughtfully analyze information provided by the services for children, other information about the person of a juvenile, usually received during the trial, bearing in mind that improper installation of such information will prevent a court from implementation of the legal requirements as to the clarification of the circumstances. This characteristics of the personality of the perpetrator can guarantee sufficient sentence, which would help to correct the person and prevent commitment of new crimes in the future.
Peculiarities of Sentencing Juvenile Offenders under the Circumstances that Mitigate Punishment
Keywords: обставини, що пом’якшують покарання; гуманізація кримінального законодавства; призначення покарання неповнолітнім; circumstances, mitigating punishment; humanization of criminal law; sentencing juveniles